Motivation of Students in the Learning English through Audio Visual Media: Qualitative Method - Moh Mahmud; Moh Izza Arrifqi; Faiqotur Rizkiyah (Darussalam English Journal, 2021)
This study aims to determine the motivation of students in learning English through audio visual media in the eleventh grade at MA Al Amiriyyah Blokagung Banyuwangi then describe how motivation is used in learning English by using audio Audio Visual Media in the form of video. Furthermore, this study also aims to determine whether it is true that it maximally motivates students by using audio visual media. This research uses a descriptive method with a qualitative design, to collect data, the researcher uses several instruments, among others; (1) Observation, (2) Questionnaire, (3) Interview. The subjects of this research were 15 eleventh grade students at MA Al Amiriyyah Blokagung Banyuwangi where these class students were placed in a special dormitory in the form of the Syafa’atul Qur’an dormitory. The results showed that (1) student motivation can be said to be in a good category, according to the results of all these findings the researcher concluded that the motivation to learn English is 80.00% of the questionnaire results which can be said to be in "good motivation". Besides, from the results of the interview, the researcher concluded that student motivation in learning English was quite good. Students' motivation to learn in English is because the atmosphere is pleasant, the teacher delivers the material well and the material is easy to understand, (2) the factors behind the motivation to learn English besides liking the atmosphere in the English classroom, the teacher also combines methods and media in carrying out the learning process, so that students felt confident that it would be easy to understand and learn the material even though they are not yet speak properly due to very minimal vocabulary,